2020
DOI: 10.3390/nu12072142
|View full text |Cite
|
Sign up to set email alerts
|

Effects on Gastroesophageal Reflux of Donkey Milk-Derived Human Milk Fortifier Versus Standard Fortifier in Preterm Newborns: Additional Data from the FortiLat Study

Abstract: Background: Feeding intolerance is a frequent diagnosis in very preterm infants. As seen in the FortiLat trial, human milk fortification with the new donkey milk-derived human milk fortifier (DF) seems to improve feeding tolerance in these infants. The aim of this study was to evaluate the effects of using the DF compared with bovine milk-derived fortifier (BF) on gastroesophageal reflux (GER) in very low birth weight (VLBW) infants. Methods: Over a total of 156 preterm infants were enrolled into the FortiLat … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Nevertheless, this last point has been intentionally avoided due to the vulnerability of preterm infants in neonatal intensive care units, that requires the preferential use of non-invasive methods of analysis. The main strengths of this study are: (i) a good match between the neonatal characteristics of the two groups, including a similar prevalence of twins in each group, that were randomly assigned either separately to each arm of the study, or to the same arm; (ii) the overall organization of the trial, that provided substantial evidence of a higher tolerability of D-HMF with respect to B-HMF infants, as supported by the different investigated parameters [18,41]; (iii) the detailed knowledge of the experimental product based on donkey milk, including the processing and manufacturing, performed by the authors specifically for the clinical trial; and (iv) the use of a balanced fortification strategy, isocaloric and isoproteic, thus limiting the effect of nutrient imbalance on the present findings.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, this last point has been intentionally avoided due to the vulnerability of preterm infants in neonatal intensive care units, that requires the preferential use of non-invasive methods of analysis. The main strengths of this study are: (i) a good match between the neonatal characteristics of the two groups, including a similar prevalence of twins in each group, that were randomly assigned either separately to each arm of the study, or to the same arm; (ii) the overall organization of the trial, that provided substantial evidence of a higher tolerability of D-HMF with respect to B-HMF infants, as supported by the different investigated parameters [18,41]; (iii) the detailed knowledge of the experimental product based on donkey milk, including the processing and manufacturing, performed by the authors specifically for the clinical trial; and (iv) the use of a balanced fortification strategy, isocaloric and isoproteic, thus limiting the effect of nutrient imbalance on the present findings.…”
Section: Discussionmentioning
confidence: 99%
“…Among diet modifications, the utility of GERD recommendations, such as thickening feeds or avoiding cow’s milk protein, remains undemonstrated in P-LPR regarding the lack of studies including infants or children with a positive diagnostic at the HEMII-pH. Similar observations may be made regarding the influence of type of milk on the occurrence of pharyngeal reflux events, because previous studies included GERD patients [ 95 , 96 , 97 ]. Smaller and frequent meals as well as sleep positioning (elevating the head of the bed) may provide benefit to infants with GERD and ‘reflux extension’ into the upper aerodigestive tract [ 6 , 98 ], but the utility of these approaches is still not demonstrated in children with only P-LPR [ 4 ].…”
Section: Therapeutic Strategiesmentioning
confidence: 98%
“…Moreover, DF reduced the occurrence of episodes of feeding intolerance, feeding interruptions, bilious gastric residuals and vomiting [25]. In an ancillary study, the use of DF reduced also the gastroesophageal reflux frequency in infants showing infants with clinical signs of gastroesophageal reflux and cardiorespiratory symptoms associated with feeding intolerance [27]. A recent urinary metabolomics investigation revealed that the different quality of the nutrients provided by isocaloric and isoproteic fortification with either DF and BF resulted in different urinary metabolic patterns [28].…”
Section: Introductionmentioning
confidence: 98%